The Socio-Cultural Mediation of Religious Authority: A Comparative Study of Halal Slaughter Fatwas in Indonesia and Australia - Ismail, Dailani; Melia Mareta, Aufa (MD Research Center, 2026)
This study highlights the gap between fatwas and the implementation of halal slaughter practices influenced by technological modernity in two distinct contexts: Indonesia as the world’s largest Muslim-majority country and Australia with its Muslim minority community.This research is the socio-cultural resistance to the machine-slaughter fatwa in Indonesia, which contrasts with the more adaptive acceptance in Australia. To analyze this paradox, the study employs a qualitative method through literature review and comparative analysis, examining fatwa documents, regulations, and societal responses in both countries. The results indicate that the effectiveness of a technological fatwa is determined not only by its legal validity but critically by its alignment with the socio-cultural character of the community. In Indonesia, resistance stems from a value clash between the efficiency logic of machines and the religious-communal character of society, whereas in Australia, an autonomous and community-driven certification system maintains Sharia integrity in manual slaughter. The conclusion emphasizes the necessity for participatory social engineering, involving intensive dialogue among scholars, industry practitioners, and the public, to design halal technologies that are not only legally valid but also spiritually and culturally meaningful, thereby ensuring harmony between religious authority, technological innovation, and societal realities.